Erradicacion de patogenos de semilla sexual de yuca (Manihot esculenta Crantz) mediante el tratamiento con microondas - Lozano, J.C.; Laberry, R.; Bermudez, A. (1987)
The effect of microwaves on the eradication of fungal and bacterial pathogens in cassava sexual seed was investigated. Healthy mature fruits were collected and dried under ambient conditions. Seeds were selected according to specific wt. by placing them in a glass of water and discarding those that floated. The selected seeds were placed in distilled water, submitted to microwave drying (2450 MHz) for 120 s and dusted with thiram (1 g/100 g seed). Colletotrichum spp., Diplodia manihotis, Fusarium spp., Cladosporium spp., Aspergillus spp., Penicillium spp., Neurospora spp., Xanthomonas campestris pv. manihotis, and Bacillus spp. were eliminated by this procedure. Germination was over 90 percent as natural seed latency was broken. The efficacy of the microwave treatment depends on the optimum temp. to be reached (77 degrees Celsius). (CIAT)